'I like to think of my comics adaptations as my own recitations … ': in conversation with Julian Peters. Issue 3 (4th May 2022) - Panhathodi, Rajesh; George, Augustine; Prasanth, Aswin
ABSTRACT: Julian Peters is a comic book artist and illustrator living in Montreal, Canada. In the last few years, he has focused on adapting classic works of English, French and Italian literature into comics. His works have been featured in anthologies, magazines, and school textbooks. Poems to See by: A Comic Artist Interprets Great Poetry (2020) is his recently published book featuring comics adaptation of 24 classic poems. His adaptations of poems by Arthur Rimbaud and François Villon were included in The Graphic Canon (Seven Stories Press, 2012), and his adaptation of T. S. Eliot's 'The Love Song of J. Alfred Prufrock' was featured in Slate Magazine . In spring 2015, he was 'Cartoonist in Residence' at Victoria University of Wellington, New Zealand. Julian holds a master's degree in Art History from Concordia University and takes his creative inspiration from the great and minor masters of all artistic periods. In this interview, Julian Peters discusses his creative process, his love for classic poetry, and his comics adaptation of his beloved poems.